PENGEMBANGAN MODEL LESSON STUDY UNTUK SEKOLAH INKLUSI SMP NEGERI DI KOTA METRO - AM, Juhri; Wibowo, Satrio Budi; Syutharidho, Syutharidho (LPPM UM Metro, 2016)
Several studies have shown that collaboration among teachers in Lesson Study (LS) activities was able to create the quality of learning mathematics more professional. Along with this, it turns out collaboration between partners becomes essential for the success of teaching special needs students (ABK) in inclusion class. Thus, in this study, researcher try to apply LS activities in the implementation of mathematics in the classroom. The aim of this study was to find out matters relating to: (1) Obtaining a complete description of the needs of the crew in mathematics, (2) Obtain an overview of the implementation lesson Study model in inclusion school, (3) Obtain package individual learning model (individual Educational Program [IEP]) for ABK in junior high school of mathematics inclusions, and (4) The implementation of the LS models in mathematics learning in the inclusion classroom. This study use the development (research development) method which consisting of five stages. In the first stage is study of literature, planning and development. In the second stage conducted LS implementation, revision, and expansion. The findings of this research are expected to be used as a reference in the implementation of LS in the inclusion classroom. In addition, provide input to the local government of Metro City in educational policy, especially in the organization of inclusion.